Analysis of an M/M/N queue with Bernoulli service schedule. (9th April 2009) - Krishna Kumar, B.; Pavai Madheswari, S.
In this paper, a Markovian multiple server queue in which each server takes vacation according to Bernoulli scheduling service has been studied. For this system, the stationary queue length distribution and several performance characteristics are obtained using the matrix geometric solution technique. The system busy period and waiting time distribution have been discussed. The 1-limited service and exhaustive service with multiple vacations have been analysed as special cases. Extensive numerical illustrations are provided.